Tuning optical dispersion and localized surface plasmon resonance of 20Li2O-xBi2O3-(78-x)TeO2-1Er2O3-1Ag glass system - Sutrisno, M.s.; Sabri, N.s.; Zaid, M.h.m.; Hisam, R. (Elsevier BV, 2023)
The optical dispersion properties of the 20Li2O-xBi2O3-(78-x)TeO2-1Er2O3-1Ag glass system were studied using the Wemple–DiDomenico fitting model. The single oscillator energy Eo and dispersion energy Ed decrease with increasing Bi2O3 concentration, with a maximum at x = 11 mol%. The large increase at x = 11 mol% can be attributed to the role of Bi2O3 as a glass former, which induces the formation of bonds in the glass network, thereby contributing to average bond strength and increasing Eo. The role of Bi2O3 as glass former may also induce minimal transformation of the glass network TeO2 to lower coordination number Nc, contributing to a maximum in Ed. Analytical expressions were also used to compute the complex dielectric properties of the glass samples. The εr and εi initially decreased at x ≤ 7 mol% before a maximum at x = 11 mol% possibly due to a decrease in polarization caused by blocking of Bi3+ ions to Li+ ions. By contrast, the maximum of εr and εi at x = 11 mol% may be attributed to the high field strength F of Bi3+ and Bi5+ ions, which increases the electronic polarizability of the glass samples. The behavior of the localized surface plasmon resonance was studied using coupling polarization approach, which revealed that the localized surface plasmon resonance of the Ag NP is dependent on the dielectric properties of Er3+ host glass. The electrical χ and Clausius–Mossotti polarizability αL showed a maximum at x = 13 mol%, which could be attributed to high real εr and imaginary dielectric constant εi, thus contributing to the polarizability of the glass samples and leading to strong localized surface plasmon resonance.